The Myth of the East Asian Miracle: The Macroeconomic Implications of Soft Budgets - Bai, Chong-En; Wang, Yijiang (American Economic Review, 1999)
The Myth of the East Asian Miracle: The Macroeconomic Implications of Soft Budgets by Chong-En Bai and Yijiang Wang. Published in volume 89, issue 2, pages 432-437 of American Economic Review, May 1999